Infrared Camera Geometric Calibration: A Review and a Precise Thermal Radiation Checkerboard Target - Ahmed ElSheikh; Bassam A. Abu-Nabah; Mohammad O. Hamdan; Gui-Yun Tian (Sensors, 2023)
Different infrared (IR) planar geometric calibration targets have been developed over the years that exploit a well-established and flexible optical camera geometric calibration procedure following the pinhole approximation. This geometric calibration is typically neglected in IR cameras, due to the relatively low resolution of thermal images and the complex IR targets needed for the geometric calibration in comparison to the optical targets. In this study, a thorough literature review of numerous IR camera geometric calibration targets, along with their respective outcomes, were summarized and leveraged to deliver a practical checkerboard target for less experienced end users, while offering the lowest reprojection errors. It was concluded that the fabrication of high emissivity contrast and precise square points of intersection within a checkerboard pattern extends the accuracy of capturing these control points in a thermal image for an optimized IR camera geometric calibration. Accordingly, two simple planar checkerboard targets were fabricated using laser engraving and ultraviolet (UV) printing technologies on a polished stainless steel (SS304) plate. The UV-printed checkerboard target on a polished metallic alloy delivered the lowest mean reprojection error <semantics>(MRE)</semantics> of <semantics>0.057</semantics> pixels and the lowest root mean square error <semantics>(RMSE)</semantics> of reprojection of <semantics>0.063</semantics> pixels, with a standard deviation lower than <semantics>0.003</semantics> pixels. The UV-printed design offers better accuracy than any other checkerboard calibration target, and comparable results to the best prominent circular pattern results reported in the literature.